Structural, optical and electrochemical performances of undoped and Sn2+-doped Bi2Te3 nanoparticles on WO3 electrodes - Buddeesao, Mirantee; Raknual, Duanghatai; Tubtimtae, Auttasit; Vailikhit, Veeramol; Teesetsopon, Pichanan (My University, 2020)
A facile synthesis approach was used to prepare Sn2+-doped Bi2Te3 nanospheres on a WO3 electrode, and the pseudo-capacitive property was measured for samples prepared with optimum parameters. SEM micrographs revealed that after the Sn2+ doping, the morphology of Bi2Te3 changed from aggregated or network-like nanoparticles to smaller nanospheres with a homogeneous distribution. The X-ray diffraction pattern showed rhombohedral Bi2Te3 coated on the WO3 electrode. Due to the more abundant electro-active sites and charge carriers that diffused through the electrolyte to the working electrode, the Sn2+-doped Bi2Te3 electrode displayed the highest specific capacity of 41.4 mAh/g at a scan rate 10 mV/s, a power density of 0.63 kW/kg, an energy density of 24.5 Wh/kg, and an LSV breakdown potential of 0.26 V. These materials may be applied in potential pseudo-capacitors and in further energy storage devices.
Keywords: Bismuth telluride; Electrochemical capacitor; Nanostructures; Semiconductors; Tin doping